2017
DOI: 10.1002/pbc.26669
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected acute renal injury after high‐dose etoposide phosphate and total body irradiation in children undergoing hematopoietic stem cell transplantation

Abstract: High-dose etoposide phosphate, a water-soluble prodrug of etoposide, may be used after total body irradiation (TBI) in pediatric allogeneic bone marrow transplantation for lymphoblastic leukemia. In a retrospective study of 21 children treated at the Nancy University Hospital (2000-2014), we identified unprecedentedly an unexpectedly high incidence (57%) of acute renal injury following etoposide phosphate infusion. Patients who developed renal function impairment experienced more severe mucositis but had outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 13 publications
1
6
0
1
Order By: Relevance
“…This retrospective study identified EP as a potential risk factor for AKI. It confirms and complements Cordero's recent findings . Checking for the occurrence of such an adverse event is particularly relevant since it has previously been demonstrated that developing AKI during SCT is more common than during other hospital treatment and represents an independent mortality risk factor in both adults and children .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This retrospective study identified EP as a potential risk factor for AKI. It confirms and complements Cordero's recent findings . Checking for the occurrence of such an adverse event is particularly relevant since it has previously been demonstrated that developing AKI during SCT is more common than during other hospital treatment and represents an independent mortality risk factor in both adults and children .…”
Section: Discussionsupporting
confidence: 88%
“…AKI is not mentioned in the summary of product characteristics of Etopophos ® . In the literature, only one report of such an adverse event has recently been published by Cordero et al., with consistent observations . AKI occurred in 12/21 (57%) patients receiving a conditioning with TBI‐EP, with a median creatinine clearance decrease of –71%, in a median delay of 36 hr, and a median recovery delay of 5 days.…”
Section: Discussionmentioning
confidence: 68%
“…Etoposide phosphate is preferred to etoposide because the latter poses a high risk of precipitation when highly concentrated . Two recent reports have highlighted the risk of acute kidney injury (AKI) due to etoposide phosphate . The Odds ratio to develop AKI linked to the use of EP at 60 mg/kg compared to cyclophosphamide at 60 mg/kg over 2 days combined with TBI was computed at 6.0 with a loss of renal function ranging between −44.5 and −71% .…”
Section: Diagram Of the Strengths Weaknesses Opportunities And Thrmentioning
confidence: 99%
“…Two recent reports have highlighted the risk of acute kidney injury (AKI) due to etoposide phosphate . The Odds ratio to develop AKI linked to the use of EP at 60 mg/kg compared to cyclophosphamide at 60 mg/kg over 2 days combined with TBI was computed at 6.0 with a loss of renal function ranging between −44.5 and −71% . The presence of an excipient in the formulation of Etopophos ® , Dextran 40 (300 mg/vial), leads us to strongly suspect this drug of being involved in the observed phenomenon .…”
Section: Diagram Of the Strengths Weaknesses Opportunities And Thrmentioning
confidence: 99%
See 1 more Smart Citation